Creation of functional solid-state composites based on black peat; IOP Conference Series: Materials Science and Engineering; Vol. 71 : International Scientific Conference of Young Scientists: Advanced Materials in Construction and Engineering, 15–17 October 2014, Tomsk, Russia - Naumova L. B.; Batalova V. N.; Gorlenko N. P.; Sarkisov Yu. S.; Kartashova A. A. Anna Aleksandrovna (Innovative technologies in building materials production, 2015)
Title screen